Racism and Beauty Standards in Indonesia: Audre Lorde's View - Dewanti, Erisa Nada; Fauzi, Ahmad; Tuzaroh, Fatimah (Pusat Studi Gender Universitas Jember, 2025)
Beauty standards are the result of social control influenced by the media. The standard of beauty circulating in Indonesia is that women are considered beautiful if they have white skin. This is contrary to the wealth of Indonesia which has various types of skin color. As a result, beauty standards give rise to racism in the form of physical insults, especially skin color for women with dark or black skin. This research aims to examine racism in Audre Lorde's